2022
DOI: 10.1108/lht-04-2022-0209
|View full text |Cite
|
Sign up to set email alerts
|

Libraries respond to the COVID-19 pandemic: drawing a science map of published articles

Abstract: PurposeThe lockdown of libraries has led to changes in the delivery of services. Reviewing many studies in this regard appears to be of great importance. Thus, this study aims to analyze the articles related to libraries and COVID-19 using the co-occurrence analysis.Design/methodology/approachThe current study is applied in terms of purpose and scientometrics in terms of type, which has been conducted using a retrospective bibliometric analysis method and drawing a science map. The relevant keywords were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…, 2022; Yu et al ., 2022b; Sung and Chiu, 2022; Meng et al. , 2023; Yi and Chiu, 2023; Guo et al ., 2021; Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al ., 2022; Adeyemi, 2021; Dong et al ., 2021; Yip et al ., 2021; Zhang et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022; Yu et al ., 2022b; Sung and Chiu, 2022; Meng et al. , 2023; Yi and Chiu, 2023; Guo et al ., 2021; Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al ., 2022; Adeyemi, 2021; Dong et al ., 2021; Yip et al ., 2021; Zhang et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the mass production of digital resources, people spend much time on electronic devices daily to obtain useful information (Cheung et al, 2022;Yu et al, 2022a;Ding et al, 2021;Wang et al, 2016). Remarkably, after the COVID-19 outbreak, people have used electronic devices to read and interact more frequently due to social distancing requirements (Chan et al, 2022;Yu et al, 2022b;Sung and Chiu, 2022;Meng et al, 2023;Yi and Chiu, 2023;Guo et al, 2021;Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al, 2022;Adeyemi, 2021;Dong et al, 2021;Yip et al, 2021;Zhang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They discovered 14 research topics in this area which can help specialists in health and medical areas to grasp the structured morphology of the current COVID-19 research. Readers may also notice our wealth of articles on bibliometrics related to COVID-19 (Li et al ., 2021a; Shueb et al ., 2022; Loan and Shah, 2022; Riahinia et al ., 2022; Zhu and Lei, 2022; Danesh et al ., 2021; Saab et al ., 2021; Allen, 2021; Yari Eili and Rezaeenour, 2023; Nadi-Ravandi and Batooli, 2023) and healthcare (Balaei-Kahnamoei et al ., 2022).…”
Section: Bibliometric Analytics For Research Topicsmentioning
confidence: 99%
“…Khazaneha et al (2022) used science mapping to explore and visualise research fields and themes to map and analyse the evolution of the coronavirus. In Nadi-Ravandi and Batooli (2022), the authors aim to investigate the articles related to COVID-19 using co-occurrence analysis, bibliometric analysis, and building a science map. Aleta et al (2019) discussed the evolution of scientific works in the field of Physics.…”
Section: Related Workmentioning
confidence: 99%